ANALYSIS OF ENHANCING THE BUSINESS ENVIRONMENT AND DEVELOPING SMALL BUSINESSES IN UZBEKISTAN BASED ON FOREIGN AND NATIONAL EXPERIENCE - Abduvoxidov , Behzod (GREEN ECONOMY AND DEVELOPMENT, 2025)
This article analyzes the business environment and small business development in the Republic of Uzbekistan. The research process involved a comparative study of foreign countries' experiences (USA, Germany, South Korea) and national practices. External and internal factors promoting the development of the business environment and small businesses have been identified, and the effectiveness of reforms implemented in Uzbekistan has been evaluated. The research results revealed regional disparities, limited access to financial resources, and insufficient mechanisms for supporting innovation. The article puts forward practical recommendations for small business development - expanding innovative activities, improving regional infrastructure, diversifying financial support, and developing public-private partnerships.